The Use of Improvised Bullet Markers with 3D CT Reconstruction in the Evaluation of Penetrating Trauma. Issue 4 (1st December 2008) - Ramasamy, Arul; Hinsley, DE; Brooks, AJ
Abstract : Radio-opaque markers placed over entry and exit wounds, have been used to help evaluate penetrating injuries and provide a permanent record of wound location on plain radiographs. To date there are no published reports of the application of improvised bullet markers in the evaluation of penetrating injuries using computed tomography (CT). We report a series of 4 cases where bullet markers were used in combination with three-dimensional (3D) computerised tomography (CT) to ascertain the path of the bullets and to assess damage to vital structures. We believe that the use of bullet markers in penetrating trauma casualties undergoing CT is valuable in the surgical decision making process and allows planning of surgical approaches.